1132 Estimation of lead exposure prevalence in korean population through combining multiple experts' judgment based on objective data sources. (24th April 2018) - Koh, Dong-Hee; Lee, Sang-Gil; Kim, Hwan-Cheol; Park, Ju-Hyun; Choi, Sangjun; Jung, Hyejung; Park, Dong-Uk
Abstract : Objectives: Estimation of exposure prevalences of carcinogens is important for preventing occupational cancers. For developing Korean CAREX (CAR cinogen EX posure) which is a carcinogen surveillance system employed in many countries, as an exemplary carcinogen, we estimated lead exposure prevalences in Korean working population. Methods: We used three nationwide data sources to retrieve objective default estimates of lead exposure prevalence across industries: the work-environment monitoring database (WEMD), the special health examination database (SHED), and the Work Environment Condition Survey (WECS). Furthermore, we surveyed experts for their judgment about lead exposure prevalence across industries after reviewing the default estimates computed from aforementioned three exposure databases. We developed various estimation methods combining experts' judgment, and then compared with each other. The 2010 Census was used as the reference population to estimate the number of lead-exposed workers for the 228 industries through multiplying the exposure prevalence with the number of workers in each industry. Results: Default estimates of exposure prevalence for 228 industries were calculated using the WEMD and SHED collected between 2009–2011, and the 2009 WECS. A total of 52 experts who have 20 or more experience in industrial hygiene practice participated in the study and provided their judgment on the lead exposure prevalences as a number for the 228 industries. Among various estimation methods, the median values of experts' responses were selected for our estimates of lead exposure prevalence in each industry. As a result, a total of 129, 247 Korean workers was estimated to be exposed to lead in the year of 2010. Conclusions: We developed a method estimating exposure prevalences combining experts' judgment based on objective databases. Our effort for estimating the exposure prevalences of CAREX may introduce an unbiased approach to the development process accounting for uncertainty of exposure.